(untitled) (Linguostylistic Studies, 2018)
The aim of the study is to reveal peculiar verbalization features of the concept of education in Ukrainian and Polish educational discourses, based on an interdisciplinary approach. The research tasks involve interpretation of the basic concepts, highlighting the essence of the interdisciplinary approach and basic components of the concept of education with a focus on the legislative-educational and educational-pedagogical contexts. The authors propose to analyze the concept of education, taking into account the basic principles of the interdisciplinary approach. This approach involves methods of linguoculturology, cognitive linguistics, pedagogical axiology, and the techniques of the cognitive-discursive, linguocultural, linguoaxiological, and praxeological approaches. The conceptual and terminological education thesaurus of Ukraine and Poland is at a challenging stage of development on the way to their integration into the European educational space. The Law of Ukraine “On Education” (2017) defines the concept of education as the basis of intellectual, spiritual, physical, and cultural development of the individual, his/her successful socialization, economic well-being, a guaranty of a society and state development united by common values and culture. In the legilature of Poland (Ustawa o szkolnictwie wyższym), education is compared to a joint public treasure. The documents focus on the lexeme quality and the need for quality development of higher education and science, which contributes to the formation of professional, ideological, and civic competencies in the relevant field of knowledge. In Ukraine and Poland, researchers demonstrate an increased interest in the praxeological aspect of the conceptual sphere of education, the main sememes of which are success, efficiency, productivity, which is, probably, due to both globalization process and mental features of every culture. The concept education is replenished with new terms like continuing education, life-long learning, knowledgable society, education capital, and with international lexemes in educational vocabulary - competence, pedeutology, andragogy, educology. In general, the concept of education combines ethnocultural and European characteristics.